The Effect of Service Quality and Location on Customer Satisfaction at Serdika Pavilion Lodging, Berastagi - Iorina Nerangisa Br Ginting; Ingan Ukur Br Sitepu; Benni Purba (Indonesian Journal of Advanced Research, 2026)
This study aims to analyze the influence of service quality and location on customer satisfaction at the Serdika Pavilion Berastagi Inn, both partially and simultaneously. The variables studied include service quality (X₁), location (X₂), and customer satisfaction (Y). This study uses a quantitative method with a descriptive approach. Data collection was conducted by distributing a questionnaire using a Likert scale to 92 respondents selected from a population of 1,201 customers in 2024 using the Slovin formula. Data analysis was performed using multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results of the study indicate that service quality and location have a positive and significant effect on customer satisfaction, with a coefficient of determination of 78.6%. These findings suggest that improving service quality, supported by a strategic location, plays a crucial role in enhancing customer satisfaction at the Serdika Pavilion Berastagi Inn.